A hypothetical evolutionary history of passalid beetles narrated by the comparative anatomy of the hindgut (Coleoptera: Passalidae) - Da Fonseca, Claudio Ruy Vasconcelos; Barbosa, Márcio Luís Leitão; Fernandez, Maria Fernanda Souza (Zootaxa, 2011)
When seen as a whole, the hindgut, more than any other section of the digestive tube, provides insights for the taxonomy of higher-level taxa of Passalidae. This comparative cladistics study utilized parsimony analyses, with 57 terminal taxa (including five outgroups) and 18 characters from the ileum of most genera of passalid beetles (Coleoptera: Passalidae), which resulted in a single tree. Based on the results and the topology of the cladogram, the following classification was adopted: (Aulacocyclinae (Solenocyclinae (Proculinae (Passalinae, Macrolininae)))). Three subfamilies (Solenocyclinae, Proculinae, and Macrolininae) are here elevated from the tribal level to the subfamily level. The subfamily Passalinae is redefined and no longer contains any tribes. The family-group name Leptaulacinae is placed in synonym with Solenocyclinae and the family-group name Ceracupedini is placed in synonymy with Aulacocyclinae.